2020
DOI: 10.1039/c9cp05697a
|View full text |Cite
|
Sign up to set email alerts
|

CO2 reactivity with Mg2NiH4 synthesized by in situ monitoring of mechanical milling

Abstract: CO2 capture and conversion are a key research field for the transition towards an economy only based on renewable energy sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The gas-solid reaction of CO 2 with alanates was investigated by Hugelshofer et al where the authors observed the formation of intermediates like aluminum formate and methoxy compounds which then got converted into methane and metal oxides as final products [11]. The influences of gas components on other metal hydrides are well investigated [12][13][14][15][16][17][18][19][20][21][22][23][24]. In this work, the influence of different ratios of CO, CO 2 , N 2 on the hydrogen storage performance of the complex metal hydride Na 3 AlH 6 with 4 mol% TiCl 3 , 8 mol% aluminum and 8 mol% activated carbon is explored.…”
Section: Introductionmentioning
confidence: 99%
“…The gas-solid reaction of CO 2 with alanates was investigated by Hugelshofer et al where the authors observed the formation of intermediates like aluminum formate and methoxy compounds which then got converted into methane and metal oxides as final products [11]. The influences of gas components on other metal hydrides are well investigated [12][13][14][15][16][17][18][19][20][21][22][23][24]. In this work, the influence of different ratios of CO, CO 2 , N 2 on the hydrogen storage performance of the complex metal hydride Na 3 AlH 6 with 4 mol% TiCl 3 , 8 mol% aluminum and 8 mol% activated carbon is explored.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 More recent studies showed that CO 2 can be reduced on the surface of hydrides that act as catalysts, by means of the Sabatier reaction allowing the conversion of CO 2 to methane and closing the cycle of carbon. [31][32][33][34][35][36][37] This allows the use of H 2 stored safely in a solid matrix (MHx, M: metal, H: hydrogen), which could acts as a catalyst for the transformation of CO 2 into a gaseous fuel. In particular, it was found that some complex hydrides such as, for example, Mg 2 NiH 4 , Mg(BH 4 ) 2 , and LiAlH 4 possess good catalytic properties for the hydrogenation of CO 2 , generating different chemical compounds of industrial interest.…”
mentioning
confidence: 99%
“…In particular, it was found that some complex hydrides such as, for example, Mg 2 NiH 4 , Mg(BH 4 ) 2 , and LiAlH 4 possess good catalytic properties for the hydrogenation of CO 2 , generating different chemical compounds of industrial interest. [31][32][33][34][35] Although the decomposition of alanates in atmospheres with CO 2 has been little explored, it is known that at temperatures greater than 120°C, LiAlH 4 reacts with CO 2 , producing CH 4 , H 2 and metal oxides.…”
mentioning
confidence: 99%
See 2 more Smart Citations